THE INFLUENCE OF WORK ABILITY, CARING BEHAVIOR, AND WORK TENURE ON THE PERFORMANCE OF INPATIENT NURSES AT NATAR MEDIKA HOSPITAL, SOUTH LAMPUNG - Putri, Riske Kharisma; Defrizal, Defrizal; Alam, Iskandar Ali (Program Studi Magister Manajemen, 2024)
This study examines the influence of work ability, caring behavior, and length of service on nurses’ performance at Natar Medika Hospital, South Lampung. The research employed a quantitative method with a cross-sectional approach and a descriptive correlational design. Data were collected using questionnaires that had been tested for validity and reliability. The findings indicate that work ability, caring behavior, and length of service have a positive and significant effect on nurses’ performance. Regression analysis revealed that these three variables account for 44.1% of the performance outcomes, while the remaining percentage is influenced by other factors. In conclusion, enhancing work ability, fostering caring behavior, and providing greater support for nurses with longer tenure can improve overall performance. Hospital management is advised to strengthen training programs, reinforce a culture of caring, and offer additional support to senior nurses.